WNT-Activated Medulloblastoma in A 6-Year-Old Boy - Prasetyo, Patricia Diana; Wahjoepramono, Eka Julianta (Medicinus, 2023)
Background: Medulloblastoma is the most common malignant brain tumor of childhood. Prognosis is mostly favorable, but may be affected by histological and molecular subtypes. Long-term therapy-related morbidity also remains a significant concern.Case Presentation: A 6-year-old boy with brainstem/midline cerebellum tumor. Histopathology found area of necrosis, sheets of malignant undifferentiated round cells with hyperchromatic nuclei and scanty cytoplasm, no nodule and no anaplasia. Immunohistochemistry found p53 wild-type staining pattern along with b-catenin diffuse cytoplasmic and focal nuclear staining. This indicated a diagnosis of WNT-activated medulloblastoma, World Health Organization (WHO) grade IV, with classic histological features.Discussion: WNT-activated medulloblastomas with classic histological features and no anaplasia were reported to have the most favorable prognosis. The current patient showed negative staining for GFAP, Olig2, EMA, H3K27M, EZHIP, and LIN28A, with retained staining for INI1 and BRG1, thus excluding several differential diagnosis such as atypical teratoid/rhabdoid tumor, embryonal tumor with multilayered rosettes, small cell glioblastoma, Ewing sarcoma, high-grade neuroepithelial tumor with BCOR alteration or diffuse midline glioma. Histopathology in combination with immunohistochemical and molecular subtyping of medulloblastoma can help to refine diagnosis, exclude differential diagnosis, and improve counseling in regards to overall prognosis.